Potential of Complementary and Alternative Medicine in Preventive Management of Novel H1N1 Flu (Swine Flu) Pandemic: Thwarting Potential Disasters in the Bud. (13th October 2010) - Arora, Rajesh; Chawla, R.; Marwah, Rohit; Arora, P.; Sharma, R. K.; Kaushik, Vinod; Goel, R.; Kaur, A.; Silambarasan, M.; Tripathi, R. P.; Bhardwaj, J. R.
Abstract : The emergence of novel H1N1 has posed a situation that warrants urgent global attention. Though antiviral drugs are available in mainstream medicine for treating symptoms of swine flu, currently there is no preventive medicine available. Even when available, they would be in short supply and ineffective in a pandemic situation, for treating the masses worldwide. Besides the development of drug resistance, emergence of mutant strains of the virus, emergence of a more virulent strain, prohibitive costs of available drugs, time lag between vaccine developments, and mass casualties would pose difficult problems. In view of this, complementary and alternative medicine (CAM) offers a plethora of interesting preventive possibilities in patients. Herbs exhibit a diverse array of biological activities and can be effectively harnessed for managing pandemic flu. Potentially active herbs can serve as effective anti influenza agents. The role of CAM for managing novel H1N1 flu and the mode of action of these botanicals is presented here in an evidence-based approach that can be followed to establish their potential use in the management of influenza pandemics. The complementary and alternative medicine approach deliberated in the paper should also be useful in treating the patients with serious influenza in non pandemic situations.